Pendaratan Otomatis Quadcopter AR Drone Menggunakan Metode Linear Quadratic Regulator (LQR) - Amroy Casro Lumban Gaol; Gembong Edhi Setyawan; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Currently quadcopter, one type of UAV (Unmanned Aerial vehicle), became one of the mobile robot technology that is widely used by humans, it's used for commercial and development of quadcopter purpose. The reason quadcopter is widely used because of its ability to maneuver in all direction and flexibility. One of the interesting thinks to develop is safe landing problem of quadcopter, due a safe landing can reduce the risk of physical damage of the quadcopter. The purpose of this research was to implement LQR, Linear Quadratic Regulator method, for safe landing the quadcopter, this method is an optimal control that produce feedback gains for linear system by minimize quadratic cost function. LQR approach is used to control the attitudes and altitude to perform quadcopter landing that are implemented in ROS, Robot Operating System. The result of this research is to produce quadcopter landing method by knowing the settling time. Landing test was performed with variety of altitude i.e. at 1m, 1.5m, 2m, 2.5m, and 3m, and based on the result of landing test, the average of settling time for landing safely is 1.75 second for increment one meter of altitude.